Condensation Recondensed: Memory Regimes in Film Adaptations - Rybina, Polina (Transcr(é)ation)

(untitled) (Western Libraries, University of Western Ontario, 2022)
Adaptations are, in a sense, multi-layered vehicles for memories of literary (or other) originals. The audience’s memories of different media versions of the classic text coexist, compete and converge, creating an extensive multi-dimensional experience. How does their memory work when readers become viewers (or vice versa) and recondense many ideas, images, and feelings linked to specific narrative worlds? The paper centres around two metaphors for memory regimes – present explicitly or implicitly – in contemporary adaptation studies. The regime of a palimpsest is based on the organic memory; it describes the individual perception of narratives: the memory of the viewer or the reader activates the intertextual “richness” of the adaptation, comparing/juxtaposing/merging different media versions of one narrative world. The regime of a network regulates the “life” of narratives in collective/cultural memory, the way meaning is ascribed to particular stories throughout the centuries, and the mechanisms of production and dissemination of narratives by the cultural industries. Metaphors help elaborate on the differentiation between the individual and the collective, the fixed and the fluid in the process of adapting, between the conventional and the contingent. Through the analyses of four film adaptations of Romeo and Juliet and a recent TV series, using the tragedy’s motifs, this paper shows how the network regime uncovers ways to make the viewer’s memory “get side-tracked”, and recall what the viewer is unlikely to remember. Via networks adaptations make their audiences remember “prosthetically” and learn more about “real” spaces with their real problems, while being initially trapped into viewing by the familiarity of old fictional stories.